The effectiveness of collaborative learning based on mobile learning in a learning management system to improve science competence in biology education students - Amaral, Casimiro Relvas; Riyanto, Yatim; Dewi, Utari; Mones, Anselmo Yata (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the effectiveness of a collaborative learning model integrated with a mobile learning-based Learning Management System (LMS) in improving science competence among Biology Education students. A quasi-experimental design with a nonequivalent control group was employed, involving 108 students from the Biology Education Program at ISC Dili, Timor-Leste, divided equally into experimental and control groups. The experimental group received treatment using a mobile LMS-based collaborative learning approach, while the control group was taught using conventional methods. Data were collected through pretest and posttest instruments and analyzed using normality, homogeneity, independent t-tests, and N-gain analysis. The findings indicate a statistically significant improvement in the experimental group’s posttest scores (M = 81.69) compared to the control group (M = 68.13), with a significance level of p = 0.001. The N-gain score of 1.14 further confirms the higher effectiveness of the experimental intervention. This study concludes that collaborative learning supported by mobile LMS is significantly more effective than traditional methods in enhancing science competence. Practical implications suggest that educators and institutions should consider adopting mobile LMS-based collaborative learning to foster deeper engagement, critical thinking, and science mastery, particularly in digitally evolving educational environments.